The Second Law of Thermodynamics as a Force Law - Schlitter, Jürgen (Entropy (Basel), 2018)
The second law of thermodynamics states the increase of entropy, [Formula: see text] , for real processes from state A to state B at constant energy from chemistry over biological life and engines to cosmic events. The connection of entropy to information, phase-space, and heat is helpful but does not immediately convince observers of the validity and basis of the second law. This gave grounds for finding a rigorous, but more easily acceptable reformulation. Here, we show using statistical mechanics that this principle is equivalent to a force law [Formula: see text] in systems where mass centers and forces can be identified. The sign of this net force—the average mean force along a path from A to B—determines the direction of the process. The force law applies to a wide range of processes from machines to chemical reactions. The explanation of irreversibility by a driving force appears more plausible than the traditional formulation as it emphasizes the cause instead of the effect of motions.